2000
DOI: 10.1068/a3139
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Contact Requirements in Producer Services Location

Abstract: In a seminal article on the relationship between the spatial structure of information flows and the location of firms, Tornqvist (1968) argued that``the most important contacts cannot be maintained with adequate efficiency by letters and telecommunications but demand direct personal contacts between personnel, and thus passenger transportation'' (page 101). Specifically, Tornqvist (1968) surmised that an essential motive force in the process of urbanization is the need for information exchange between increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…One source is the conceptual foundation laid by Scott who established they were integrated internally by the movement of goods (and people) and externally by world trade, both of which involve logistics activity. That foundation is enriched by the thinking on the location of outsourced producer services, a production arrangement central to the understanding of global city activity in the research of Sassen (1994) and extended by the research on services of Daniels and Bryson (2002) and Goe et al, (2000). Outsourcing has recently become a very significant part of logistics services as Skjoett-Larsen (2000) and Makukha and Gray (2004) have shown.…”
Section: Logistics Activity and Global City Regionsmentioning
confidence: 98%
“…One source is the conceptual foundation laid by Scott who established they were integrated internally by the movement of goods (and people) and externally by world trade, both of which involve logistics activity. That foundation is enriched by the thinking on the location of outsourced producer services, a production arrangement central to the understanding of global city activity in the research of Sassen (1994) and extended by the research on services of Daniels and Bryson (2002) and Goe et al, (2000). Outsourcing has recently become a very significant part of logistics services as Skjoett-Larsen (2000) and Makukha and Gray (2004) have shown.…”
Section: Logistics Activity and Global City Regionsmentioning
confidence: 98%
“…One such key factor is the presence of structural attributes that allow firms in producer services industries to realize the benefits of agglomeration (Scott 1988): that is, the benefits of being located close to required labor, business expertise, and other needed inputs, as well as a larger number of customers. In many types of producer services, provision typically requires face-to-face interaction between vendors of a service and their clients (Goe et al 1999;Irwin and Kasarda 1991). Moreover, the success of firms in producer services industries is often based on access to strategic business information and knowledge that their clients do not possess, as well as access to specialized labor (Beyers 1989;Palmer et al 1990).…”
Section: Factors Influencing the Growth And Concentration Of Producermentioning
confidence: 99%
“…It has been suggested that spatial clustering would improve the economic performance of producer services by enabling service providers to tap into a localized "collective learning" process. In contrast with the earlier theorization of agglomeration economies that focused on static cost reduction, the new approach has placed greater emphasis on how local environment or location generates dynamic processes to enhance the innovativeness and productivity of collocated firms (Bennett & Smith, 2002;Coe, 1998;Cook et al, 2007;Goe, MacPherson, & Phillips, 2000;Isaksen, 2004).…”
Section: Introductionmentioning
confidence: 91%